The relationship between rewards and employees motivation among employees at Pejabat Tanah Dan Jajahan Machang / Nur Diana Natasya Che Khalid - Che Khalid, Nur Diana Natasya (2014)
The purpose of this study was to identify the relationship between rewards and employees motivation among employees at Pejabat Tanah dan Jajahan Machang. This study was conducted at Pejabat Tanah dan Jajahan Machang, Kelantan. The findings were obtained from data collected through the questionnaire distributed personally to the respondents. The finding was analyzed by using Package in the Social Science Software (SPSS) version 19.0. Section A contains the findings of the demographic profile of respondents. The elements involved were gender, age, educational level and length of service. Section B contains the type of reward that influences employee motivation such as bonus and promotion. Section C contains information about employee motivation level that contributes to employee work performance and employee retention.